Evaluation of technological properties and selection of wild lactic acid bacteria for starter culture development. (15th December 2022) - Abarquero, D.; Renes, E.; Combarros-Fuertes, P.; Fresno, J.M.; Tornadijo, M.E.
Abstract: Sixty-six lactic acid bacteria strains, isolated from traditional cheeses, were identified by MALDI-TOF technology, characterised through the evaluation of their enzymatic activities (acidifying and proteolytic capacities and carboxypeptidase, aminopeptidase, dipeptidase and esterase activities) and selected through a scoring system based on activity results in order to select wild strains of technological interest for cheese manufacturing. The strains were identified as Lactococcus lactis (9), Leuconostoc citreum (3), Leuconostoc mesenteroides (2), Leuconostoc pseudomesenteroides (1), Levilactobacillus brevis (7), Lactiplantibacillus plantarum (32), Lactiplantibacillus paraplantarum (7) and Lacticaseibacillus paracasei (5). In general, Lactococcus lactis strains showed the highest degree of acidifying activity, especially in the first hours of fermentation, and extracellular proteolytic activity. In contrast, intracellular activities, assayed from cell-free extracts, were higher in the lactobacilli strains. L. paracasei strains showed the highest level of aminopeptidase activity, while some L. plantarum strains obtained high values of dipeptidase activity. Carboxypeptidase activity was very low or undetectable in many strains, although in others the activity values were exceptionally high. Esterolytic activity was generally low, although L. paracasei strains showed higher activity on short-chain substrates. Finally, 11 strains were selected using the scoring system that could be used in the design of starter cultures and co-cultures. Graphical abstract: Image 1 Highlights: Fermented dairy products are a reservoir of strains with technological potential. The enzimatic activity is a useful tool for selecting indigenous LAB strains. Selection of lactococci is made on the basis of their acidifying activity. Selection of lactobacilli, is based on their proteolytic and peptidase activity. Eleven LAB strains were selected for having the best technological properties.